2008
DOI: 10.1590/s1516-89132008000200014
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction period of Mimagoniates microlepis, from an Atlantic Forest Stream in Southern Brazil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
(13 reference statements)
1
7
0
1
Order By: Relevance
“…Small individuals, with less swimming capacity, larval forms and/or eggs could be more easily dragged than the larger fishes, which could migrate to upstream regions. Patterns like this were proposed by other authors such as Menezes and Caramaschi (1994) and Braga et al (2008) for the coastal river species. Similar longitudinal segregation was proposed for Astyanax janeiroensis Eigenmann, 1908, other Characidae related to Atlantic forest streams, where an upstream spawn migration and downstream drag of eggs and larval forms were described (Mazzoni et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Small individuals, with less swimming capacity, larval forms and/or eggs could be more easily dragged than the larger fishes, which could migrate to upstream regions. Patterns like this were proposed by other authors such as Menezes and Caramaschi (1994) and Braga et al (2008) for the coastal river species. Similar longitudinal segregation was proposed for Astyanax janeiroensis Eigenmann, 1908, other Characidae related to Atlantic forest streams, where an upstream spawn migration and downstream drag of eggs and larval forms were described (Mazzoni et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…This study found a short reproductive period. Although the Ribeirão stream basin presents a strong flood pulse that causes changes of habitat structure (Gonçalves and Aranha, 2004;Braga et al, 2008;Vitule et al, 2008), such floods occurs in a well defined seasonal way (mainly January, February and March). It seems that D. langei in some way adapted itself to anticipate those events.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those descriptors, Dei Tos et al (2002) used the index of reproductive activity (IRA), a method that 820 combines the proportion of reproducing individuals and values of gonadosomatic index to evaluate the reproductive activity for the whole fish assemblage or single populations. Although the IRA has been broadly applied for fresh water fish assemblages (Dias et al, 2005;Bailly et al, 2008;Braga et al, 2008), few studies used this index to describe reproductive activity of marine fish (Souza & Chaves, 2007;Rodrigues-Filho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there are some species that exhibit a very seasonal and restricted breeding period, usually reproducing during spring and summer (e.g. Pimelodella pappenheimi, Bryconamericus microcephalus, Mimagoniates microlepis, Deuterodon langei) (Amaral et al, 1998;Mazzoni & Silva, 2006;Braga et al, 2006Braga et al, , 2008Vitule et al, 2008a). Flash floods occur mainly on early months of the year, so it seems that these species are adapted to these events and they spawn just before summer rains.…”
mentioning
confidence: 99%